RETHINKING AND REPOSITIONING THE UNIVERSITY AS CADRE AND ACTIVIST FOR THE POST-APARTHEID STATE: EVIDENCE FROM RURAL SOUTH AFRICA - Mafukata, Mavhungu Abel (PEOPLE: International Journal of Social Sciences, 2019)
This paper investigated the role of the post-colonial-apartheid university in (South) Africa using a case study sourced from Vhembe District, Limpopo Province to back its argument. A mixed method approach blending secondary data obtained from reviewed sources, and participant interviews was used to collect data. Three (n=3) doctoral studies conducted in the area were found and reviewed accordingly. Key Informant Interviews (KIIs) and Focus Group Discussions (FGDs) were held with various participant stakeholders. Collected data were recorded as field notes for analysis, and analysed using the thematic analysis method. This paper was guided by the theories of decolonization and Africanisation of post-colonial-apartheid (South) African universities. The results revealed that the post-colonial-apartheid university undermined and sidelined African indigenous knowledge. African indigenous communities were also impeding knowledge development because of their refusal to divulge information. Furthermore, universities had difficulty conducting ethical and usable research. The paper concludes that the university has a role to play in the post-colonial-apartheid era provided it transforms to become relevant for the course.